2006
DOI: 10.1002/smj.557
|View full text |Cite
|
Sign up to set email alerts
|

Beyond dichotomy: the curvilinear relationship between social responsibility and financial performance

Abstract: A central and contentious debate in many literatures concerns the relationship between financial and social performance. We advance this debate by measuring the financial–social performance link mutual funds that practice socially responsible investing (SRI). SRI fund managers have an array of social screening strategies from which to choose. Prior studies have not addressed this heterogeneity within SRI funds. Combining modern portfolio and stakeholder theories, we hypothesize that the financial loss borne by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

42
766
5
15

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,097 publications
(828 citation statements)
references
References 86 publications
42
766
5
15
Order By: Relevance
“…2. This finding is somewhat supported by the findings of Barnett and Salomon (2006) who have found a similar curvilinear relationship between social responsibility and financial performance in the context of stockmarket data.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…2. This finding is somewhat supported by the findings of Barnett and Salomon (2006) who have found a similar curvilinear relationship between social responsibility and financial performance in the context of stockmarket data.…”
Section: Discussionsupporting
confidence: 79%
“…The existence of curvilinear impacts has been tested in the literature beyond EP and FP, for example, in the case of knowledge creation (Badar et al 2015) and in fairness perceptions in job satisfaction (Janssen 2001).Thus, we argue that existing levels of EP positively moderate the link between EP and FP, which implies a curvilinear (quadratic) relationship. This notion is somewhat supported by a recent study on the link between social performance and financial performance (Barnett and Salomon 2006) that found evidence for a curvilinear relationship in the context of mutual fund investments.…”
Section: The Case For Curvilinear Relationships Between Ep and Fpmentioning
confidence: 70%
See 2 more Smart Citations
“…In addition, Spearman's rank correlation coefficient only assesses linear relationships but some relationships can be curvillinear (Barnett and Salomon 2006). Earlier research has shown that lack of correlation does not imply lack of causation (Howard and Maxwell 1980;Wright et al 1999;Verhulst et al 2012).…”
Section: Discussionmentioning
confidence: 99%